Research on Dynamic Resource Allocation Strategy for Embedded FPGA Reconfigurable System Development Based on Innovation of Analog Mixed Signal Integrated Circuit and RF High Frequency Circuit Technology - Shi, Baichuan (Scientific Journal of Technology, 2025)
In the context of the integration of semiconductor technology and intelligent systems, embedded FPGA reconfigurable systems have become a key carrier for innovation in analog mixed signal integrated circuits (AMS ICs) and RF circuits due to their flexibility and high performance. This article takes a management perspective and focuses on the dynamic resource allocation challenges of such complex R&D projects. By constructing a three-dimensional analysis framework of "technical characteristics resource requirements configuration mechanism" and combining typical cases in the semiconductor industry, a resource prediction model based on digital twins, a dynamic scheduling algorithm based on agile iteration, and an interdisciplinary knowledge network collaboration mechanism are proposed. Research has shown that the heterogeneity of analog mixed signals and RF high-frequency technology poses special requirements for the professional adaptability of R&D resources. The iterative development mode of reconfigurable systems requires real-time response capabilities for resource allocation, and the integration of digital twin technology and knowledge graph can effectively improve resource allocation efficiency. This study provides theoretical reference and practical path for resource management of high-tech R&D projects.